Gizmo Is a Mean Word!. (1st April 2015) - Koltai, Peter J.
Abstract : The editorial titled "Gizmos" in the April issue of Otolaryngology–Head and Neck Surgery was unfortunate. Intracapsular tonsillectomy is a rational surgical option for managing tonsillar hypertrophy causing obstructive sleep apnea in selected children. It is performed routinely by surgeons across the globe and has become the standard of care across northern Europe due to the high safety profile of the operation. The semirigid, dartlike design of the sinuplasty devices suggested the idea for an airway‐specific set of high‐pressure balloons. We began working on these in 2007 and had FDA approval in 2009. They are in wide use by many airway surgeons. Lingual tonsils are a frequent cause of obstructive sleep apnea, and there is no tool that manages this as effectively as endoscopic plasma ablation. We are all engaged in an honorable effort to improve care; surgical and creative skills are as important as analytical skills. Both are necessary for the continuous improvement of our work. Both are worthy of respect.